2021
DOI: 10.1111/jth.15453
|View full text |Cite
|
Sign up to set email alerts
|

Detection of right ventricular dysfunction in acute pulmonary embolism by computed tomography or echocardiography: A systematic review and meta‐analysis

Abstract: Background Right ventricular (RV) dysfunction predicts worse outcomes in acute pulmonary embolism (PE). Because computed tomography (CT) pulmonary angiography visualizes cardiac structures, it is a potential method for assessing RV function without the delays associated with inpatient echocardiography. Objectives We conducted a systematic review and meta‐analysis to assess the diagnostic accuracy of CT scan findings for detecting RV dysfunction compared with echocardiography. Methods We searched MEDLINE and EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
(124 reference statements)
0
12
0
1
Order By: Relevance
“…PPVs and NPVs were suboptimal for the use of echocardiography as a stand-alone test for decision making. Recently, a systematic review and meta-analysis showed that RVD can be detected by computed tomography (CT) imaging; the diagnostic accuracy of CT compared with echocardiography varies depending on specific findings [ 82 ]. The assessment of multiple CT findings of RVD seems to have improved diagnostic accuracy compared to stand-alone findings.…”
Section: Discussionmentioning
confidence: 99%
“…PPVs and NPVs were suboptimal for the use of echocardiography as a stand-alone test for decision making. Recently, a systematic review and meta-analysis showed that RVD can be detected by computed tomography (CT) imaging; the diagnostic accuracy of CT compared with echocardiography varies depending on specific findings [ 82 ]. The assessment of multiple CT findings of RVD seems to have improved diagnostic accuracy compared to stand-alone findings.…”
Section: Discussionmentioning
confidence: 99%
“…An individual patient-level meta-analysis of 6 prospective cohort studies that included 2874 normotensive patients with PE reported that right ventricular dysfunction was associated with an increased risk of death, shock, or recurrent PE (OR, 2.28 [95% CI, 1.58-3.29) . A systematic review of 21 studies (11 prospective and 10 retrospective) that included 3111 patients reported that compared to the criterion standard of echocardiography, an increased right ventricular:left ventricular ratio greater than 1.0 had a sensitivity of 83% and a specificity of 75% for right ventricular dysfunction . Patients with 1 or more signs of right ventricular dysfunction on imaging and elevated cardiac biomarker (troponin, brain natriuretic peptide [BNP], or N-terminal pro-BNP) are defined as intermediate-high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…64 A systematic review of 21 studies (11 prospective and 10 retrospective) that included 3111 patients reported that compared to the criterion standard of echocardiography, an increased right ventricular:left ventricular ratio greater than 1.0 had a sensitivity of 83% and a specificity of 75% for right ventricular dysfunction. 65 Patients with 1 or more signs of right ventricular dysfunction on imaging and elevated cardiac biomarker (troponin, brain natriuretic peptide [BNP], or N-terminal pro-BNP) are defined as intermediate-high-risk patients.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In recent years, several studies have focused on evaluating the severity and prognosis of APE based on right ventricular parameters/functions assessed using CTPA. [4][5][6] Several studies have examined atrial parameters in APE 7,8 ; in contrast, left ventricle (LV) parameters have not been studied as extensively. Furthermore, to date, no reports on such evaluations in older patients have been published.…”
mentioning
confidence: 99%
“…Moreover, it has become the first-line imaging method for APE. In recent years, several studies have focused on evaluating the severity and prognosis of APE based on right ventricular parameters/functions assessed using CTPA 4–6 . Several studies have examined atrial parameters in APE 7,8 ; in contrast, left ventricle (LV) parameters have not been studied as extensively.…”
mentioning
confidence: 99%